Non-linear Instability and Plastic Collase of Partially Loaded Spherical shells - Habip, L.M. (Engineering Transactions, 1975)
Based on a two-dimensional discretization scheme, finite-difference energy method is utilized for the non-linear, elastic and elastic-plastic collapse analysis of spherical shells under external pressures acting asymmetrically on a given fraction of the shell surface. The results are compared with some of the limited experimental data and theoretical predictions previously available.